Respuesta :

Oj2

Answer:

Step-by-step explanation:

X3 - 2x2 -24x

Pulling out tje terms 3.1 pull out like factors.

X3 - 2x2-24x =x(x2-24)

Trying the factor by spitting the middle term

3.2 factoring x2 -2x-24

The first term is x2 its coefficient is 1

The middle is -x2 its coefficient is -2

The last term is constant is -24

Multiple the coefficient of the first term by the constant 1 .-24=-24

Find the to factors of -24 whose sum eqyals the coefficient of the middle term which is -2

-24+1=-23

-12+2=-10

-8+4= -2

A d tbe final results: ×.(×-6)

Give me a five star if you got it